Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5999/aps.2017.00885
|View full text |Cite
|
Sign up to set email alerts
|

Serial Tissue Expansion at the Same Site in Pediatric Patients: Is the Subsequent Expansion Faster?

Abstract: BackgroundSerial tissue expansion is performed to remove giant congenital melanocytic nevi. However, there have been no studies comparing the expansion rate between the subsequent and preceding expansions. In this study, we analyzed the rate of expansion in accordance with the number of surgeries, expander location, expander size, and sex.MethodsA retrospective analysis was performed in pediatric patients who underwent tissue expansion for giant congenital melanocytic nevi. We tested four factors that may infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…That means an increased number of expansions will induce greater flexibility, but the the larger expander will restrict the expansion rate. 21 In 2020, Kim et al reviewed the medical records of 88 patients with tissue expander reconstruction, including 33 patients with serial expansion. By comparing single and serial expansion techniques, Kim et al concluded that infection and revisional operation rates were significantly higher in the serial expansion group than in the single expansion group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That means an increased number of expansions will induce greater flexibility, but the the larger expander will restrict the expansion rate. 21 In 2020, Kim et al reviewed the medical records of 88 patients with tissue expander reconstruction, including 33 patients with serial expansion. By comparing single and serial expansion techniques, Kim et al concluded that infection and revisional operation rates were significantly higher in the serial expansion group than in the single expansion group.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a positive correlation between the number of surgeries and the expansion rate; a negative correlation between the large expander size and the expansion rate. That mean an increase number of expansions will induce greater flexibility, but the the larger expander will restrict the expansion rate [21]. In 2020, Kim LJ et al reviewed the medical records of 88 patients with tissue expander reconstruction, including 33 patients with serial expansion.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For huge nevi (i.e., lesions over 20 cm in diam- eter), the insertion of multiple tissue expanders does not always result in a satisfactory amount of tissue, and second-stage expansion is often required at the same site. Some reports have stated that using more expanders could increase the expansion rate; however, obtaining sufficient flexibility of the tissue still required another operation, even when multiple expanders were inserted [8]. Thus, it must be accepted that serial expansion is unavoidable in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Serial expansion aims to overcome the limitations of expansion in terms of the available surrounding tissue during the early stages of tissue expansion [7]. Recently, serial expansion has been suggested as a way to increase the expansion rate and has been proposed as a surgical option [8]. Although several reports have demonstrated the safety and efficacy of tissue expansion, there are concerns about infection, device exposure, and flap tissue loss.…”
Section: Introductionmentioning
confidence: 99%